(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the role of the works of Amon Mukhtar in the development of Uzbek prose of the 20th-21st centuries. The themes and characters of the author’s novels, art, and sources of influence are analyzed. His role in the development of the novel is explained.